Weichang'an Formula Inhibits Tumor Growth in Combination with Bevacizumab in a Murine Model of Colon Cancer-Making up for the Deficiency of Bevacizumab by inhibiting VEGFR-1 - Chuan-Fang Pan; Xi Zhang; Xi Zhang; Jing-Wen Wang; Tao Yang; Linda L. D. Zhong; Ke-Ping Shen (Frontiers Media S.A., 2020)
Aim: Angiogenesis plays an important role in the initiation, development, and metastasis of malignant tumors. Antiangiogenic drugs combined with immune therapy are considered to have a synergistic effect on anti-tumor strategy. Weichang'an formula (WCAF) is a prescription of traditional Chinese medicine (TCM) based on pharmaceutical screening and clinical experience. The aim of this study is to examine the effect of WCAF and its combined action with Bevacizumab (BEV) in colorectal cancer, and to identify the possible mechanism of action.Methods: A human colon cancer cell (HCT 116) subcutaneous xenograft model was established in BALB/c-nu/nu mice. Tumor-bearing mice were randomized into each of four groups: control, WCAF treated, BEV treated, and WCAF plus BEV treated. Apoptosis was detected by TUNEL assay. Western blot was used to assess the protein levels of Leptin-R, STAT3, p-STAT3, BCL-2, and VEGFR-1. Immunohistochemistry was used to detect the micro-vessel density (MVD) and AKT1. Leptin and Vascular endothelial growth factor A (VEGF-A) mRNA expression were detected by Real-time PCR (RT-PCR). A network pharmacology study and validation assay were carried out to find the underlying molecular targets of WCAF related to immune regulation.Results: Compared with the control group, WCAF reduced tumor weight and volume, as well as promoted tumor cell apoptosis. WCAF treatment decreased the mRNA expression of Leptin and VEGF-A, while the protein levels of CD31, LEP-R, VEGFR-1, STAT3, and p-STAT3 were decreased in tumor tissues. In addition, VEGFR-1 protein expression was decreased in the WCAF group and the WCAF plus BEV group but not in the BEV group. The combination of WCAF and BEV demonstrated a partial additive anti-tumor effect in vivo. The pharmacological network also found there are 26 WCAF target proteins related to cancer immune and 12 cancer immune related pathways. The AKT1 protein expression in the WCAF and WCAF + BEV groups were significantly lower than the that in the control group (p < 0.01).Conclusion: WCAF can inhibit tumor growth and promote apoptosis and inhibit tumor angiogenesis in subcutaneous xenografts of human colon cancer HCT-116 in nude mice. WCAF also makes up for the deficiency of BEV by inhibiting VEGFR-1. The VEGFR-1 expression between the combination group and BEV alone achieved statistically significant difference (p < 0.01). Combined with BEV, WCAF showed a partial additive anti-tumor effect. The mechanism may be related to Leptin/STAT3 signal transduction, VEGF-A, VEGFR-1 and WCAF target proteins related to cancer immune such as leptin and AKT1.